Efficacy of treatment of cattle with the pyrethroid alphamethrin in preventing infestation by Dermatobia hominis - Sanavria, Argemiro; Grisi, Laerte (Pesquisa Agropecuaria Brasileira, 1991)
The treatment of cattle by spraying an aqueous emulsion of alphamethrin (FMC 65318) at concentration of 50 ppm (0.005%) showed an efficacy of 100% in preventing Dermatobia hominis infestation up to 18 days after treatment, based on artificial challenge using thirty larvae of first stage. Average number of third stage larvae which developed from the challenge on day 3, 7 and 18 within controls were 9, 15 and 13, respectively.
Keywords: warble fly; prevention